Performance of MR-De'Duster in Capturing Low Density Particulate. Issue 1 (July 2020) - Hussein, Norelyza; Yusof, Mohd Rashid Mohd; Jamian, Nor Ruwaida; Hashim, Nor Hasyimah; Hassan, Che Hafizan Che; Zaidi, Nur Syamimi
Abstract: A newly multi-cyclones named MR-deDuster is developed to capture particulate emission from potential industries. This study aims to assess the performance of MR-deDuster in capturing low density particulate. The tested particulate used in the study is PreKotTM (proprietary of AMR Sdn. Bhd), which is a low density particulate available in the market and commonly used as a pre-coating material with particulate density of 747 ± 2.2 kg/m 3 . Fractional collection efficiency, overall collection efficiency, cut diameter (dpc ) and stack concentration were used to determine the performance of unit. The study indicates the unit able to capture about 88% of low density particulate at volumetric gas flow rate of 0.19 m 3 /s. The study has shown that collection efficiency of MR-deDuster increased as the volumetric gas flow rate increased. However, as the volumetric flow rate of gas was further increased to 0.21 m 3 /s, the collection efficiency of the unit was reduced. The optimum collection efficiency was observed to occur at volumetric gas flow rate of 0.19 m 3 /s.